Increasing the efficiency of a drone motor by arranging magnetic sheets to windings - Mitsuhide Sato; Masami Nirei; Yuichiro Yamanaka; Tatsuki Suzuki; Yinggang Bu; Tsutomu Mizuno (Energy Reports, 2020)
In recent years, there has been an increase in motorization; therefore, the demand for high-efficiency motors in automobiles and aircrafts will further increase. A drone is an aircraft that flies without a human pilot onboard; it has a short flight time because the size of the mounted battery is limited. The magnetic sheet consists of a composite material with magnetic powder and silicone rubber. The eddy current loss and copper loss of the drone motor reduces when the sheet is attached to the coil. This paper reports on the effect of improving the drone motor efficiency by lowering the leakage magnetic flux of the rotor and increasing the heat dissipation in the simulation and the experiment.
Keywords: 330; Thermal conductivity; Copper loss; Magnetic composite material; Magnetic sheets; Motor; Stray load loss